The ultimate guide to your microscope - Levine, Shar, 1953-; Johnstone, Leslie (New York : Sterling, 2008)
Explains the basics of using a microscope and creating slides and includes instructions for activities which explore forensics, bugs and animals, water, food, and plants.
Includes index.
Library Media Connection.
School Library Journal starred.
Science Books & Films (A.A.A.S.).
6.0
3-6
Keywords: Microscopes -- Juvenile literature; Microscopy -- Juvenile literature; Microscopes; Microscopy; Microscopes